1980
DOI: 10.1093/bja/52.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Benzodiazepines for Oral Premedication in Minor Gynaecological Surgery

Abstract: Diazepam 10 and 20 mg, lorazepam 2.5 and 5.0 mg, flunitrazepam 1 and 2 mg, and a placebo, were compared in a randomized double-blind controlled trial as oral premedication for 210 patients undergoing minor gynaecological surgery. Flunitrazepam 1 mg and lorazepam 2.5 mg were superior to placebo (P less than 0.001 and P less than 0.05 respectively) in relieving patient anxiety when assessed by a trained observer 60 min after premedication. Flunitrazepam 1 mg also produced more drowsiness (P less than 0.01) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Therefore, investigations on strategies to reduce preoperative anxiety deserve further investigation. Although some studies have demonstrated that BZDs are effective in reducing anxiety before surgery [30,35], these drugs are not a substitute for enhancement of coping skills and increased knowledge with regard to the peri-operative course.…”
mentioning
confidence: 99%
“…Therefore, investigations on strategies to reduce preoperative anxiety deserve further investigation. Although some studies have demonstrated that BZDs are effective in reducing anxiety before surgery [30,35], these drugs are not a substitute for enhancement of coping skills and increased knowledge with regard to the peri-operative course.…”
mentioning
confidence: 99%
“…All drugs tested are claimed to be fairly fast absorbed after oral intake and about an hour is a common time lapse in similar previous research studies (8)(9)(10). There are a number of other studies that have been unable to show any major effects of small doses of oral benzodiazepines as compared to placebo (8)(9)(10)(11)(12)(13)(14). In larger doses an anxiolytic effect has been proven but at the risk for a prolonged sedative effect and recovery time (12,14,15).…”
Section: Discussionmentioning
confidence: 85%
“…In larger doses an anxiolytic effect has been proven but at the risk for a prolonged sedative effect and recovery time (12,14,15). In two previous studies of lorazepam 2.5 or 5 mg, pronounced sedative effects were seen within one hour but still only marginal anxiolytic effect (10,13). There are also others who have failed to find any significant differences as regards anxiolysis between intramuscular premedication with other active drugs and placebo (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The hypnotic effect of flunitrazepam the night prior to surgery has been confirmed in earlier studies (5-9). Other investigators have found oxazepam (10-13) and flunitrazepam (9, 10, [14][15][16][17][18][19] useful as prernedication. Pakkanen et al (10) studied the hypnotic, sedative, cardiovascular and unwanted effects in a comparison between oxazepam 30 mg and flunitrazepam 1 mg.…”
Section: Discussionmentioning
confidence: 99%